Common Change of Complete Blood Count Parameters in COVID-19: a Literature Review - Kevin S Dhinata (Universitas Kristen Maranatha, 2021)
The rising number of COVID-19 all around the world caused a drastic increase in theoccupancy rate of healthcare facilities, triggering overload in some places. This situationrequires healthcare workers to evaluate patients’ conditions and conduct risk stratificationefficiently, especially in a triage situation. Complete blood count is a widely available,economically affordable, and time-efficient testing method which may be significant in assistingthose processes. This review article analyzes changes in complete blood count parameters inCOVID-19 with the aim to identify the common changes in the parameters in COVID-19 patientsand their relation to the disease progression and severity. COVID-19 patients commonlyexperienced anemia, increased red blood cell distribution width, decreased white blood cellcount, significant changes in white blood cell differential count, and thrombocytopenia. It isunderstood that changes in complete blood count parameters and their extent may providevaluable information about the disease severity and prognosis. In conclusion, COVID-19 patientsshare a common pattern of complete blood count parameters alterations which is related to thedisease progression, severity and prognosis. It is expected that complete blood count examinationmay play a major role in COVID-19 management, given the valuable information provided bythe examination.Keywords: complete blood count; COVID-19; erythrocyte; leukocyte; platelet